Modelling the Complexity of Measurement Estimation Situations: A Theoretical Framework for the Estimation of Lengths (mathematica didactica, 2022)
Abilities in estimation are important for everyday life, and investigated with different research interests. Although quite different estimation situations were used, studies usually did not address the question of task characteristics systematically. This paper presents a theoretical model that may serve as a basis for the task design in length estimation. First, key features of length estimation tasks were extracted by analyzing the literature. Second, these elements are varied systematically. Third, they are combined, reanalyzed, and reduced. This procedure results in a model of 228 meaningful situations for length estimation. The model may also serve as an analytical tool for comparison of studies.